Body Matters in Emotion: Restricted Body Movement and Posture Affect Expression and Recognition of Status-Related Emotions - Reed, Catherine L.; Moody, Eric J.; Mgrublian, Kathryn; Assaad, Sarah; Schey, Alexis; McIntosh, Daniel N. (Frontiers in Psychology, 2020)
Embodiment theory suggests that we use our own body and experiences to simulate information from other people’s bodies and faces to understand their emotions. A natural consequence of embodied theory is that our own current position and state contributes to this emotional processing. Testing non-disabled individuals, we investigated whether restricted body posture and movement influenced the production and recognition of nonverbal, dynamic emotional displays in able-bodied participants. In Experiment 1, participants were randomly assigned to either unrestricted or wheelchair-restricted (sitting, torso restrained) groups and nonverbally expressed six emotions (disgust, happiness, anger, fear, embarrassment, and pride) while being videotaped. After producing each emotion, they rated their confidence regarding how effectively they communicated that emotion. Videotaped emotional displays were coded for face, body, and face+body use. Based on naïve coders’ scores, both unrestricted and wheelchair-restricted groups produced emotionally congruent face and body movements and both groups were equally confident in their communication effectiveness. Using videos from Experiment 1, Experiment 2 tested non-disabled participants’ ability to recognize emotions from unrestricted and wheel-chair restricted displays. Wheelchair-restricted displays showed an overall decline in recognition accuracy, but recognition was selectively impaired for the dominance-related emotions of disgust and anger. Consistent with embodied emotion theory, these results emphasize the importance of the body for emotion communication and have implications for social interactions between individuals with and without physical disabilities. Changes in non-verbal emotion signals from body restrictions may influence social interactions that rely on the communication of dominance-related social emotions.